Neo-Liberalism in Theorizing World Politics Post Cold War: The Evolution and Impact of Neo-Liberalism in World Politics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Neo-Liberalism as a theory mechanism is understood as positivist approach or behavioral and is an extension of Liberalism in scientific way. It is the structure which focuses on economic character, global economy and political structure. Neo-Liberalism is an overarching structure of capitalism and under this structure there are many economic institutions such as IMF, WTO, INGO, TNC, MNC et al. They highlight interdependence as complex interdependence which emerges out of the structure that shapes the behavior of States as one can see how European Union, WTO, SAARC and other international organizations determines the behavior of States. However before obtaining into Neo-Liberalism, one must have a glimpse of Liberalism and how it has evolved over a period of time to be called as Neo-liberalism. This essay endeavors to scrutinize the evolution of Liberalism to Neo-Liberalism and how it has become a dominant phenomenon post-cold war outlining its characteristics, pivotal development in the current world order which has been wielded by countries across the globe and its current position. I will also address the development post 911 and Arab Spring to understand contemporary issues and location of Neo-liberalism and how it has shaped the world politics theoretically.